2015
DOI: 10.1001/jamapsychiatry.2014.2022
|View full text |Cite
|
Sign up to set email alerts
|

Depression Outcomes Associated With an Intervention Implemented in Employment Training Programs for Low-Income Adolescents and Young Adults

Abstract: IMPORTANCE Recent estimates indicate that 6.5 million adolescents and young adults in the United States are neither in school nor working. These youth have significant mental health concerns that require intervention. OBJECTIVE To determine whether a mental health intervention, integrated into an employment training program that serves adolescents and young adults disconnected from school and work, can reduce depressive symptoms and improve engaged coping strategies. DESIGN, SETTING, AND PARTICIPANTS A quasi-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Nonetheless, the novel moderation effect of motivation to reduce depression is consistent with prior research on patients’ response to CB treatment (Keijsers et al, 1999) and the moderation effect of substance use on MDD onset was medium in magnitude, which increase confidence in these results. Our finding that higher baseline depressive symptoms amplify the intervention effects has previously emerged in multiple trials (e.g., Jaycox et al, 1994; Spence et al, 2003; Tandon et al, 2015), thus providing greater confidence in its reliability.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Nonetheless, the novel moderation effect of motivation to reduce depression is consistent with prior research on patients’ response to CB treatment (Keijsers et al, 1999) and the moderation effect of substance use on MDD onset was medium in magnitude, which increase confidence in these results. Our finding that higher baseline depressive symptoms amplify the intervention effects has previously emerged in multiple trials (e.g., Jaycox et al, 1994; Spence et al, 2003; Tandon et al, 2015), thus providing greater confidence in its reliability.…”
Section: Discussionsupporting
confidence: 54%
“…Meta-analyses indicate that programs targeting participants with high initial symptoms typically produce stronger depressive symptom reductions than universal programs (Horowitz & Garber, 2006; Stice et al, 2009). Individual trials have also found that symptom reductions in prevention trials are stronger for participants with high versus low baseline symptoms (e.g., Jaycox, Reivich, Gillham, & Seligman, 1994; Spence, Sheffield, & Donovan, 2003; Tandon et al, 2015; Wilksch & Wade, 2014). Theoretically, those with elevated symptoms have greater potential to show symptom reductions.…”
Section: Individual Factorsmentioning
confidence: 99%
“…More young people should be trained in professional/technical and ‘soft’ skills, which may also enhance optimism. Second, reducing NEET youths’ depression, anxiety and substance abuse problems by providing them with mental health services may enable them to more effectively cope with challenges, develop confidence in their abilities, and take better advantage of training and back‐to‐work opportunities (Cook, ; Tandon et al., ). Third, it will be critical to identify and provide enhanced educational guidance to young adolescents (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Current practice guidelines recommend psychotherapeutic interventions in the treatment of mild to moderate depression, bipolar disorder and alsoas regards cognitive behavioural psychotherapy (CBT) -in the treatment of psychotic disorders and schizophrenia [10]. Several types of vocational interventions have also been developed to prepare young adults with mental disorders for competitive employment, and earlier research has recommended integrating vocational interventions into clinical treatment to facilitate return to work [12,17,18,19]. The participation rates in both implemented and planned interventions seem low, considering that the young adults in the studied group were granted a fixed-term work disability pension that aimed at return to work or education after rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the integration of vocational services may be beneficial for psychiatric treatment results [17]. A major problem may be related to poor integration between interventions and clinical care.…”
Section: Discussionmentioning
confidence: 99%